Вера, Надежда, Любовь...: женские портреты : [25 знаменитых женщин последних двух столетий] / Ю. Безелянский - Безелянский Юрий Николаевич (Радуга, 1998)
Экземпляры: аб. ЦБ (2000) / Инвентарный номер: 37995 / Цена: / Сис.шифр: 63.3(2)5 / Авт.знак: Б39 / ГРНТИ: 03.19 / ББК: 63.3(2)5-297